Systematic review on the compliance of WHO guidelines in the management of patients with advanced HIV disease in Africa: The case of cryptococcal antigen screening - Zuhura Mbwana Ally; Jackline Vicent Mbishi; Mariam Salim Mbwana; Hafidha Mhando Bakari; Swalehe Mustafa Salim; Zarin Nudar Rodoshi; Muhidin Ibrahim Hundisa; Rebecca Mesfin Sileshi; Biruk Demisse Ayalew; Rahma Musoke; Lynn Moshi; Yousef Elias Fakhoury; et al. (PLoS ONE, 2025)
Background The World Health Organization (WHO) recommended cryptococcal antigen (CrAg) screening for people presenting with advanced HIV disease (AHD) and for those with positive CrAg without evidence of meningitis to initiate preemptive antifungal medication. Data on the implementation of WHO recommendations regarding CrAg screening is limited. We estimated pooled prevalence of CrAg screening uptake, cryptococcal antigenemia, lumbar puncture, cryptococcal meningitis and initiation of preemptive antifungal medication from available eligible published studies conducted in Africa. Methods PubMed, Cochrane Library and Embase were searched for articles published between January 2011 and December 2023. CrAg uptake was defined as percentage of eligible people (CD4 ≤ 200 cells/mm3 or WHO stage III/IV) who received cryptococcal antigen testing. Stratified analysis to compare uptake and cryptococcal antigenemia between studies that involved multiple vs single sites was performed. Using random effects models, we computed the pooled estimate of CrAg screening uptake, cryptococcal antigenemia, lumbar puncture, cryptococcal meningitis, preemptive antifungals treatment and 95% confidence intervals (CIs). Results Ten studies with 18,820 individuals with AHD were analyzed. Overall, the pooled estimate of CrAg screening uptake was 57.1% (95% CI: 41.4–72.7). CrAg screening uptake was significantly lower among studies that involved multiple sites compared to those that involved single site, (47.3% vs 73.3%; p<0.001). Overall, the pooled prevalence of cryptococcal antigenemia was 9.6% (95% CI:6.4–12.9). Cryptococcal antigenemia was significantly lower among studies that involved multiple sites compared to those that involved single site, (9.1% vs 10.4%; p<0.001). Among those who tested positive for CrAg, 84.6% (95% CI: 54.1–99.0) received preemptive antifungal treatment, though nearly 25% did not undergo lumbar puncture, highlighting gaps in diagnostic follow-up. Six studies evaluated CrAg positive patients with lumbar puncture and the overall prevalence of lumbar puncture was 74.9% (48.0–94.8). The overall prevalence of cryptococcal meningitis was 58.1% (46.6–69.6). Conclusions Not screening for CrAg among people with AHD and failure to initiate antifungal medications among eligible patients with cryptococcal antigenemia presents a significant missed opportunity. Emphasis on improving CrAg screening is critical given its proven cost-effective benefits.